Friction and wear characterization of LIPSS and TiN / DLC variants - L., Rathmann; T., Rusche; H., Hasselbruch; A., Mehner; T., Radel (Applied surface science, 2022)
[Display omitted] •This work shows that TiN and DLC coating can be used in combination with LIPSS to reduce wear compared to untextured reference sample.•The properties of different texture-coating variants are examined and discussed.•Sessile drop tests and pin-on-disk tests were performed to investigate wetting and wear behaviour.•Consequently, texture-coating variants can simultaneously preserve the hydrophilic properties of the LIPSS and reduce the friction in pin-on-disk tests. LIPSS and their hydrophilic attributes are subject to severe wear as soon as they are in direct tribological contact. A possible protection is offered due to the combination of LIPSS and hard coatings. However, the influence of the process sequence (direct and indirect texturing) on tribological properties of the resulting texture-coating variants are not well studied. Therefore, this work presents results of water lubricated pin-on-disk tests of LIPSS-DLC and LIPSS-TiNx variants. The pins were made of X5CrNi18-10 while the substrates consisted of X153CrMoV12 with a hardness of 250HV. The results demonstrate that a firstly textured and then with DLC coated substrate halves the coefficient of friction in comparison to other texture-coating variants to 0.1. Otherwise, a firstly textured and then with TiNx coated substrate shows the lowest wear track depth of 2 µm. Consequently, texture-coating variants can simultaneously preserve LIPSS’ hydrophilicity and enhance the tribological behavior of pre-treated substrates under water lubrication.